LMP-1 IMMUNOHISTOCHEMICAL DETECTION OF EPSTEIN - BARR VIRUS IN LYMPHOMA AMONG SUDANESE PATIENTS - BakhitYousif, Ibrahim; Mohammed Yousif, Yousif; Mohammed, SideegAbd Elaziz (International Journal of Research -GRANTHAALAYAH, 2015)
Several studies have suggested a probable etiologic association between Epstein-Barr virus (EBV) and lymphoma; multiple EBV proteins can be expressed in infected lymphocytes, among which Latent membrane protein-1(LMP-1) is thought to be most important for malignant transformation, the aim of this study was to investigate the association of LMP-1 EBV in this tumors. This study was carried at the Radio Isotope Center Khartoum (RICK)- Khartoum state –Sudan from January 2015 to July 2015, it was retrospective and prospective, the study include ninety (90) Formalin –fixed paraffin embedded biopsies from which seventy (70) of malignant lymphoma (study group) and twenty (20) lymph node hyperplasia (control group ). EBV was detected in (32%) (23/70), and (10%) (2/20) respectively, the (P.value =0.04), this result showed a significant difference between case and control groups, the, there is no statistically significant difference between the two lymphoma subtypes Hodgkin’s and Non-Hodgkin`s the (P.value= 0.333). There is sufficient evidence for the carcinogenicity of EBV in the causation of lymphoma in Sudan. This requires further evaluation to find out whether this positivity is due to co-infection or has a role in pathogenesis.